O Framework Geodesign aplicado ao Quadrilátero Ferrífero (Minas Gerais/Brasil) - Pedro Benedito Casagrande (2018)
Geology has always been present in the process of transformation of the anthropic landscape. However, the role of Geology in landscape planning is still incipient and has not been the subject of an integrated policy. Linked to this and to the need of professionals related to Geology and Mining to participate actively in planning, the Geodesign technique was chosen to elaborate an alternative future plan for the Iron Quadrangle region, in Minas Gerais, Brazil, using Geology as base. In this way, a Geodesign Workshop was held with several professionals related to Mining and obtained a territorial plan for the region. This result generated the Decision Model, which is consistent with the study area and showed that the method used is assertive for landscape and territory planning.